Pelatihan Kader Posyandu Tentang Pemeliharaan Kesehatan Gigi Dan Mulut Pada Pasien Diabetes Melitus - Wirata, I Nyoman; Astiti, Ni Komang Erny; Suarniti, Ni Wayan; Purnamayanti, Ni Made Dwi; Suindri, Ni Nyoman; Mahayati, Ni Made Dwi (Jurnal Pengabdian kepada Masyarakat Nusantara, 2025)
Diabetes mellitus is one of the predisposing factors for periodontal disease. The prevalence of diabetes mellitus in the population aged ≥15 years in the city of Denpasar is 1.8%. The increase in cases of diabetes mellitus is also accompanied by an increase in cases of periodontal disease every year. in 2023 the distribution of diabetes mellitus cases according to location is mostly in Dangin Puri Kangin village, with a total of 41 cases (20%). The purpose of this community service activity is to improve the understanding and knowledge of Posyandu cadres on how to maintain dental and oral health in diabetes mellitus patients. The Community Service Method is carried out by providing training to Posyandu cadres regarding dental and oral health maintenance in diabetes mellitus patients using lecture, discussion, question and answer and demonstration methods, as well as evaluation using pre-test and post-test. This community service activity has a positive impact on the understanding and improvement of Posyandu cadres' knowledge regarding education for diabetes mellitus patients in maintaining dental and oral health. The conclusion is that the training participants understand the training material well, and the Posyandu cadres have good knowledge in maintaining dental and oral health in diabetes mellitus patients